Beyond Marx and other entries - Gleicher, David, 1949- (Studies in critical social sciences, 2018)
Beyond Marx and other entries' is a truly original book by David Gleicher, author of 'The Rescue of the Third Class on the Titanic: A Revisionist History' (Liverpool University Press, 2006). It explores deep areas of semiotics, joined with economics, anthropology, sociology, history and philosophy and political science, even Franz Kafka's literary works. These are communicated by entries, based primarily on Gleicher?s actual blog 'Looking through the crack' from 2013 to 2017. No other book quite compares to it, but one might equate it to impressionist art, or the?one and the many.? Each entry is independent; nothing in one makes even an allusion to another. The readers however cannot help but to make connections themselves and understandings of dystopian possibilities.